Reentry support in Victoria, Australia: managing risk, or fostering agency?. Issue 1 (2nd January 2023) - Kennedy, K.; Sandy, L.; Martinovic, M.
Abstract: More than half of Australia's prison population have experienced prior incarceration. Factors such as homelessness, mental illness, and poverty compound the challenges of reentry. Reentry support in Victoria, Australia is state funded, yet delivered via three non-governmental organizations. In this article we explore practitioners' experiences of working with people who were incarcerated in the liminal phase of reentry—where one is neither prisoner nor citizen but in-between. Practitioners reported trust and rapport are the central pillars of practice and choose to utilize strengths-based approaches instead of risk-based approaches, but felt that service brokerage is impeded by associated professionals' concerns around risk.